Peran Budaya Lokal Terhadap Literasi Matematika Siswa Sekolah Dasar di Cirebon - Mahpudin Mahpudin; Yuyu Yuliati (Proceedings of The ICECRS, 2019)
Local culture in certain regions has a big role in shaping the characteristics and characteristics of the members of the community. Likewise in terms of mathematical literacy, the cultural elements of the local community often contain mathematical concepts within it which are able to play a role in the effort to develop mathematical literacy abilities. In the context of classroom learning, local culture can be used as content in teaching mathematics so that it becomes easier to grow students' mathematical literacy skills. This paper examines how the role of local culture in mathematical literacy in elementary school students in the Cirebon region by studying the cultural content and local wisdom that exist in Cirebon society and linking it with students' mathematical literacy.